NOVEL QUERCETIN NANOEMULGEL OPTIMIZATION: GELLING AGENTS EVALUATION AND THE APPLICATION OF RESPONSE SURFACE METHODOLOGY - RINI NASTITI, CHRISTOFORI MARIA RATNA; DWIASTUTI, RINI; RISWANTO, FLORENTINUS DIKA OCTA (International Journal of Applied Pharmaceutics, 2023)
Objective: This current research aimed to examine the profile of a range of gelling agents by applying principal component analysis (PCA) based on certain physical properties and to develop a novel optimized nanoemulgel formulation containing quercetin (QUE). Methods: A series of gelling agents with different concentrations were grouped and profiled by applying the PCA based on their viscosity and the spreadability. Based on the profile, one of the gelling agents was selected to be formulated in QUE nanoemulgel. The formulation of QUE nanoemulsion was then fabricated using a spontaneous emulsification method involving triacetin as the oil phase, a combination of Kolliphor® RH 40 and Transcutol® as the surfactant-cosurfactant system, and citrate buffer pH 6 as the aqueous phase. QUE nanoemulgel was fabricated by incorporating the gelling agent (sodium carboxymethylcellulose; Na CMC) into the nanoemulsion. The composition of Kolliphor® RH 40, Transcutol®, and Na CMC in the formulation was further optimized by using Box Behnken Design followed by a response surface methodology provided by Minitab®. Results: The PCA grouped a range of gelling agents into three principal components (PC) based on the concentration, viscosity and spreadability. The results of PCA showed that Na CMC was the most suitable gelling agent for QUE nanoemulgel. To optimize the QUE nanoemulgel formulation, sixteen runs of BBD were successfully fabricated, providing an optimum-validated composition of 21.45 g, 13.96 g, and 4.00 g for Kolliphor® RH 40, Transcutol®, and Na CMC, respectively, with composite desirability of 0.843. Conclusion: We successfully conducted gelling agent profiling by providing three types of PC using PCA. An optimized and validated formulation of QUE nanoemulgel was also successfully designed as a potential topical diabetic wound healing formulation.